The remembering candle - Goldberg, Alison (Barefoot Books, 2025)
A peaceful celebration of the memories our loved ones leave with us when they pass. I was sad when Grandpa died. I think about how sad Mom was too. Mom says she misses Grandpa, but all her memories are like shining lights. Grandpa died last November. Now, one year later on the anniversary of his death, a boy and his family light a special candle. It's not a birthday, Hanukkah, or Shabbat candle. It's a yahrzeit candle in remembrance of him, and it will burn all night and all day tomorrow until sunset. But why does it burn for so long? The boy and his family spend the next night and day remembering Grandpa and sharing stories with each other. From his stylish hats, to piano duets, and apple squares for dessert, warm memories of Grandpa shine like stars with them while the yahrzeit candle burns -- and continue to shine when it goes out.